Postmodern referentiality - Pompe, Gregor (Muzikološki zbornik, 2013)
Petar Bergamo's Second symphony (1967) must be analyzed in the context of Zagreb Biennale and therefore in the context of modernist domination which Bergamo understood as cul-de-sac. His Second symphony is conceived as set of quotations and allusions that are able to trigger wide filed of associations connected to the logic of music history. Such a procedure resemble postmodernist technique, therefore it is possible to understand Bergamo's symphony as a proto-postmodern work.
Keywords: Bergamo, Petar, 1930-; intertekstualnost; Intertextuality; kontekst; modernizem; postmodernizem; referencialnost; tekst